2021
DOI: 10.3389/fpubh.2021.644235
|View full text |Cite
|
Sign up to set email alerts
|

A COVID-19 Crisis in Child Physical Fitness: Creating a Barometric Tool of Public Health Engagement for the Republic of Slovenia

Abstract: The Republic of Slovenia implements the largest longitudinal database of child physical fitness in the world–SLOfit. Slovenia has some of the most physically active children globally, and it has responded rapidly to incorporate national physical activity (PA) interventions throughout the COVID-19 pandemic. Despite aggressive campaigns to maintain PA at home, the country has seen a tremendous decrease in child physical fitness over the past several months as self-isolation measures have been mandated by nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 25 publications
4
75
1
1
Order By: Relevance
“…The measures taken had a direct impact on the data obtained. Similar to our study, the decreased level of physical activity of children during the pandemic and online teaching were also reported for children in other countries, such as Slovenia [33], Canada [34], Spain, and Brazil [35]. A decreased level of physical activity was followed by longer screen time, less time outdoors [34], and increased sleep duration [35].…”
Section: Discussionsupporting
confidence: 88%
“…The measures taken had a direct impact on the data obtained. Similar to our study, the decreased level of physical activity of children during the pandemic and online teaching were also reported for children in other countries, such as Slovenia [33], Canada [34], Spain, and Brazil [35]. A decreased level of physical activity was followed by longer screen time, less time outdoors [34], and increased sleep duration [35].…”
Section: Discussionsupporting
confidence: 88%
“…The world is getting hotter ( 2 ), children are becoming less fit and more obese ( 3 ), and the likelihood of vector-borne diseases entering the human population is also increasing ( 1 ), rendering the possibility of future movement restrictions to novel disease outbreaks likely, itself creating a vicious-cycle of isolation, physical de-training ( 4 ), and increased risk for heat injury ( 5 ), especially for vulnerable populations like children. There needs to be greater priority given when considering children's health when creating public health policy ( 6 ), especially since the extraordinary impact the COVID-19 pandemic has had on human movement will likely not be a one-off situation.…”
Section: Introductionmentioning
confidence: 99%
“…From the earliest days of this COVID-19 pandemic, researchers have been sounding the alarm on how the negative impacts of isolation, confinement, and physical (in)activity will affect all persons ( 4 ), and children in particular ( 7 ). Problematically, most governments remain either unaware or unconcerned about the effects self-confinement have on the physical and mental health of its citizens ( 6 ). Jurak et al have outlined the grave costs these restrictive measures have had on the physical fitness of children in Slovenia, noting that their research group has observed greatest decrease in child fitness in the >30 year history since systematic surveillance of child fitness began ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the second lockdown, however, unorganized PA fell to less than half of the level of the first lockdown, and organized PA was as low as 3.7 min per day [13]. The data of the nationwide, school-based physical fitness surveillance program "SLOfit" in Slovenia documented a dramatic drop in fitness in both boys and girls [14].…”
Section: Introductionmentioning
confidence: 99%